2009
DOI: 10.2478/s11756-009-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

UV-B radiation and selenium affected energy availability in green alga Zygnema

Abstract: Green alga Zygnema was exposed to three concentrations of selenium and two levels of UV-B radiation. The combined effects of both treatments on energy availability; photochemical quantum yield and respiratory potential were studied. Our findings show that traces of selenium enhance metabolic process connected with photochemical quantum yield and mitochondrial respiration. Surprisingly, selenium does not diminish the effects of UV-B radiation; on the contrary, the combined action of UV-B radiation and traces of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
10
2
Order By: Relevance
“…Increased ETS activity in hybrid buckwheat by the addition of Se is in line with fi ndings that the addition of Se to Vigna radiata enhanced respiratory as well as succinate dehydrogenase activity and the involvement of Se in mitochondrial membrane functions (Easwari and Lalitha 1995). Germ et al (2009) also observed that Se is involved in activation of energy resources in green alga Zygnema sp.…”
Section: Plant Partsupporting
confidence: 83%
“…Increased ETS activity in hybrid buckwheat by the addition of Se is in line with fi ndings that the addition of Se to Vigna radiata enhanced respiratory as well as succinate dehydrogenase activity and the involvement of Se in mitochondrial membrane functions (Easwari and Lalitha 1995). Germ et al (2009) also observed that Se is involved in activation of energy resources in green alga Zygnema sp.…”
Section: Plant Partsupporting
confidence: 83%
“…Folin–Ciocalteu) were used for a more imprecise determination [e.g. 18, 20, 41]. The presence of such phenolics, which are not common in freshwater microalgae, supports the hypothesis that their production might be crucial in UV protection of Zygnema .…”
Section: Discussionmentioning
confidence: 99%
“…Even in polar regions, Zygnema is quite common and easy to recognise due to its mat-forming growth [25, 31, 40]. As mentioned, no harmful effect of experimental UV exposure on Zygnema was observed in previous studies [20, 31], yet, the nature of UV protection in Zygnema remains unknown. We expect that the alga obtains UV resistance by the accumulation of phenolic compounds, which can be analysed by high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effects of UV radiation on Zygnematophycean green algae (e.g., Meindl and Lütz 1996; Lütz et al 1997; Holzinger et al 2009; Germ et al 2009; Pichrtová et al 2013; Stamenković and Hanelt 2014; Prieto-Amador 2016; Stamenković and Hanelt 2017). Pichrtová et al (2013) investigated the changes in phenolic compounds in three species of Zygnema from either Arctic or Antarctic habitats.…”
Section: Introductionmentioning
confidence: 99%